An Application to Wireless Standards for Remote Monitoring For Electric Drive Systems Using Zigbee Standards - Korani Ravinder, MD Abdul Khader, Zeesha, Imthiazunnisa Begum, Mohammed Qayamuddin (International Journal of Scientific Research and Management (IJSRM), 2013)
This paper discusses an implementation of wireless standards for remote monitoring ofelectric drives. An appropriate wireless system has been developed and described. It uses ZigBeestandard for remote data transmission combined with Internet connectivity for assessment of the Globalnetwork-collected information. The designed measuring devices and the respective sensors are alsopresented. Algorithms have been developed allowing evaluation of additional parameters using datafrom the measurements held. Detailed experimental studies confirm the good performance of thismonitoring system. The research carried out as well as the results obtained can be used in design andset up of such types of wireless monitoring systems. Keywords––Intelligent sensors, End-device,Coordinator device, ZigBee network, Measurement system, Remote monitoring